Design and Build Student Majors Application Using Simple Additive Weighting Method at GIKI 2 Surabaya High School Based on Website - Angelina, Novi Dewi; Nurcahyawati, Vivine; Rahmawati, Endra (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
The process of majors that occur at this time the school is sorting the value of students by eliminating students according to the interests that students have chosen, then the result of the grouping will be compared again with the number of UN are sorted from highest to lowest UN value and will be compared with TPA value and psychotest result. The result of the sorting is the highest value of TPA, interest majors choosing IPA, the number of the highest value of the UN will enter the SCIENCE department in accordance with the remaining IPA class quota will go to the Department of IPS. The student majors have several problems, one of them, it takes 2 weeks to sort the studentsÂ  grades so that they can exceed the date limit set by the school. Based on the problems, SMA GIKI 2 Surabaya need an application that can support in the process of student classes are timely and accurate using the Simple Additive Weighting method. Based on existing solutions, it will generate a website based student program that can help the BK section manage the data, perform student majors, and report generation.